2023
DOI: 10.1002/adma.202211742
|View full text |Cite
|
Sign up to set email alerts
|

Chloride‐Based Additive Engineering for Efficient and Stable Wide‐Bandgap Perovskite Solar Cells

Abstract: Metal halide perovskite based tandem solar cells are promising to achieve power conversion efficiency beyond the theoretical limit of their single‐junction counterparts. However, overcoming the significant open‐circuit voltage deficit present in wide‐bandgap perovskite solar cells remains a major hurdle for realizing efficient and stable perovskite tandem cells. Here, a holistic approach to overcoming challenges in 1.8 eV perovskite solar cells is reported by engineering the perovskite crystallization pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 59 publications
0
32
0
Order By: Relevance
“…Compared with 3C-FAPbI 3 of 1.409 eV, the band gap increases by about 0.013 eV, indicating that chloride ions mainly increase the band gap of 3C-FAPbI 3 single crystal caused by MACl additives. 24,36,49,50 Figure 7d presents the average results of multiple measurements: about 2% chlorine contributes to an increase of about 0.01 eV in the band gap. In comparison, 1% MFAI is associated with an increase of about 0.003 eV, whereas about 7% MA cations has almost no influence on the band gap.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with 3C-FAPbI 3 of 1.409 eV, the band gap increases by about 0.013 eV, indicating that chloride ions mainly increase the band gap of 3C-FAPbI 3 single crystal caused by MACl additives. 24,36,49,50 Figure 7d presents the average results of multiple measurements: about 2% chlorine contributes to an increase of about 0.01 eV in the band gap. In comparison, 1% MFAI is associated with an increase of about 0.003 eV, whereas about 7% MA cations has almost no influence on the band gap.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Note that the Thierry Pauporté group also first discovered the existence of these MFAI reaction products between different concentrations of MACl additives and FAPbI 3 perovskites after high-temperature annealing in the devices . Surprisingly, until now, only a handful of studies have reported the formation of MFAI from the MACl additive, which is widely used in high-efficiency FA-based PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Rathnayake et al 18 have developed a polarizable AMOEBA force field 25 for the CsPbI 3 -solvent system, enabling the study of crystal nucleation, growth, and ion solvation in the CsPbI 3 solutions. 18,26,27 Pols et al 19 have developed a ReaxFF force field for CsPbI 3 and have used it to investigate the degradation of CsPbI 3 at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…To adequately settle the above-mentioned problems, enormous efforts have been taken toward the development of various passivation materials to heal imperfections, modulate perovskite crystallization and improve the efficiency and stability of PSCs. Additive engineering has been known as a feasible and effective method to passivate defect sites and directly regulate the morphology of perovskite for fabricating high-crystallinity, low-defect-density, large-size-grain perovskite film. In the early studies, a series of monofunctional Lewis bases mediators with O and N heteroatoms such as PMMA, quinoline and pyrrole have been successfully adopted to chelate with uncoordinated Pb 2+ , which was believed as the main source of charge traps . For example, Li et al employed the quinoline with the intention of passivating the internal defects of perovskite, where the nitrogen atom anchors the uncoordinated Pb 2+ via coordinate bond, thereby neutralizing the excess positive charge in the crystal .…”
Section: Introductionmentioning
confidence: 99%